EURO-ATLANTIC SECURITY AND THE ECONOMICFINANCIAL IMPLICATIONS OF THE CONFLICT IN UKRAINE - DINCĂ, Marian; DINCĂ, Alexandru-Marian (International Journal of Legal and Social Order, 2022)
Euro-Atlantic security has always been a priority in the international security environment, especially at the beginning of the 21st century, when mankind is facing a complex, dynamic and unpredictable security environment, one of profound economic and social imbalances. The conflict in Ukraine is, and will remain, a hot topic and the maximum interest because of its global political, social and economic-financial implications.